Soil and colloidal phosphorus dynamics in three ky soils: bioavailability, transport and water quality implications - Makris, Konstantinos C. (My University, 2003)
Particulate P constitutes a significant portion of the total P found in surface runoff water. Water dispersed P-containing particles can travel long distances via surface runoff and reach water bodies causing decrease in water quality. The main objective of the study was to evaluate the potential facilitation of P transport by the water dispersed soil colloids (WDC) using three KY soils with a long-term record of poultry manure, and fertilizer P applications. Sequential fractionation for both whole soils and colloidal samples revealed that the WDC had a greater total and labile P content than the soil as a whole. Also, application of manure and fertilizer P seemed to decrease colloidal organic P fractions and increase the inorganic P fractions over the period of a growing season (May to September). Laboratory settling kinetics experiments were set up for the clay-colloidal fractions of the soils. It was shown that particulate P fractions paralleled WDC settling kinetics whereas dissolved P fractions remained in solution even after 36 hours. Field taken intact soil cores were leached with colloidal suspensions to test the effect of WDC on the vertical P movement. Results illustrated the preferential flow of particulate P though the macropores. When water was applied to the manure amended soil, dissolved P levels increased significantly over the control. WDC additions lowered dissolved P levels to the manure-amended columns, by sorbing to the WDC particles, but still greater than the dissolved P levels of the columns that had not been applied with manure.
Keywords: Soil Phosphorus; Water Dispersed Colloids; Fractionation; Water Quality